Peningkatan Pemahaman tentang Tumbuhan melalui Aktivitas Berkebun pada Anak Usia Dini di TK Tenripakkua Kabupaten Bone - Putri Damayanti; Irwandi Rahmat; Rezki Rezki; Nurlaeliana Nurlaeliana; Hasmatang Hasmatang (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2023)
Early Childhood is a period when children will be more sensitive to receive various stimuli given. Every child born must have potential, therefore, from a young age they must be given a stimulus for all potential intelligence of children both physically and mentally. Introduction to plants through gardening activities for early childhood is used as one of the lessons to stimulate children's development because plants are learning media that are very easy to find in the surrounding environment making it easier for children to interact directly with the surrounding environment. This will make it easier for children to recognize and understand the importance of plants in everyday life and also stimulate children's thinking skills. This service was carried out at TK Tenriapakkua. Media soil in pots can also be used for gardening activities on land that is not large. The methods used in community service are socialization and demonstration methods. High enthusiasm was shown by students when gardening and being able to distinguish the parts of plants.